PERLINDUNGAN HAK- HAK PASIEN DALAM PELAYANAN KESEHATAN BERDASARKAN PERUNDANG-UNDANGAN YANG BERLAKU - Takdir, Takdir (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
Protection of the rights of patients to protect patients and their rights of legal violations and abuse of rights. There been many laws that really protect patients rights explicitly and obviously, including: Act No. 8 of 1999 on the protection of consumers, chapters 1, 4, 7, 19, 23, 45, dan 46, 47, 48, and 63. , Act No. 23 of 1992 on health, chapters 4, 5, 53, 54.55., government Regulation 26 of 1960 on oath of Physicians and still stout again. With the juridical basis over the protection of patients rights can be carried out strictly in order to become a major solution to integration and enforcement of patients rights in health care